A cachaça nos rituais afro-brasileiros: cantos, crenças e curas em terreiros de umbanda Uberlândia–MG (2012 –2017) - Silva, Floriana Rosa da (2018)
The present research intends to discuss the ritual uses of cachaça – the sugar cane licquor – in Afro-Brazilian cults of Umbanda. The empirical locus of the work is the city of Uberlândia, located in the region of Triângulo Mineiro, in Minas Gerais. It analyzes six sacred grounds, located in different districts of the city. Field research has developed over the years 2016 and 2017, and has produced and collected a wide range of data and documentary evidence, including audio visual and imagery records. The problematization started from the perception that the cachaça has representations as "negative" as "positive", constructed historically in accordance with the socioeconomic and political interests. Nevertheless completely different representations hatch from the interior of cultural practices peculiar to the popular strata, related to the experiences of the sacred, especially in the cults of African matrix. Nonetheless, we chose Umbanda because, among the more than 218 spaces destined for the Afro-Brazilian cult of Uberlândia, it represents more than half of the places. In addition, their rites and practices are often touched, reproduced and absorbed in various Candomblé and Umbanda Omolocô sacred ground. The research showed that in all the temples dedicated to the Umbanda and Umbanda Omolocô, the cachaça occupies a fundamental place. When leaving the daily life of the bars and botequins and entering the space of the temples the cachaça is sacralized, becoming the instrument that makes possible the contact with the sacred and the catalyzing ingredient of the healing recipes promoted by the entities, through the phenomenon of possession. Theoretically, our work was based on concepts pertinent to the reflections placed on History and Culture, such as representations, imaginary, sacred, profane, ritual and popular culture.